2016
DOI: 10.1002/ecy.1576
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria facilitate parasite epidemics in Daphnia

Abstract: The seasonal dominance of cyanobacteria in the phytoplankton community of lake ecosystems can have severe implications for higher trophic levels. For herbivorous zooplankton such as Daphnia, cyanobacteria have poor nutritional value and some species can produce toxins affecting zooplankton survival and reproduction. Here, we present another, hitherto largely unexplored aspect of cyanobacteria, namely that they can increase Daphnia susceptibility to parasites. In a 12-year monthly time-series analysis of the Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 60 publications
3
37
0
Order By: Relevance
“…It has been recently shown that Caullerya prevalence in Greifensee is correlated with cyanobacterial blooms, and experimental evidence has supported this facilitation (Tellenbach et al. ). However, if clones of Daphnia are differently susceptible to cyanobacteria (Hietala et al.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…It has been recently shown that Caullerya prevalence in Greifensee is correlated with cyanobacterial blooms, and experimental evidence has supported this facilitation (Tellenbach et al. ). However, if clones of Daphnia are differently susceptible to cyanobacteria (Hietala et al.…”
Section: Discussionmentioning
confidence: 92%
“…; Tellenbach et al. ). Moreover, in a previous three‐month survey of a Daphnia population infected with Caullerya in lake Rimov (Czech Republic), random and infected subsamples of Daphnia population significantly differed in their clonal composition (Yin et al.…”
mentioning
confidence: 98%
See 3 more Smart Citations